2007
DOI: 10.1007/s10680-007-9144-4
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Changes in the Incidence of Care Need in West Germany Between 1986 and 2005

Abstract: In Germany, the share of the older population has been continuously growing. Is the increase paralleled by a rising number of frail people, however? In search of an answer, we analyse the development of care need incidence in West Germany between 1986 and 2005 on the basis of longitudinal data from the German Socio-Economic Panel (SOEP). The results show a lower transition risk to care need for each successive cohort when all degrees of care need are taken into account. However, no change occurs when only seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Hypothesis 2: However, based on the previous hypothesis and on earlier research that points towards a compression or equilibrium scenario [ 30 , 49 ], we expect that this is also true in most – but not all – counties.…”
Section: Introductionmentioning
confidence: 85%
“…Hypothesis 2: However, based on the previous hypothesis and on earlier research that points towards a compression or equilibrium scenario [ 30 , 49 ], we expect that this is also true in most – but not all – counties.…”
Section: Introductionmentioning
confidence: 85%
“…Recent studies investigating the current and predicted state of health of people aged older than 60 years have, however, have shown conflicting results. Some predicted a decrease in disability in elderly populations compared to previous generations [ 16 18 ], while others indicated that increasing life expectancy will be accompanied by an increase in disability among people older than the age of 60, mainly due to a higher incidence of chronic diseases [ 19 , 20 ]. Finally, some studies have predicted a reduction in the number of older people with moderate and severe disabilities, and a growing proportion of older people with mild disabilities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies on current and past trends in health expectancies, including disability-free and active life expectancy [37]. They have shown improvements in health expectancies for Germany and other developed countries as measured by different indicators of limitations in the activities of daily living or of subjective health perceptions [38][39][40][41]. However, other studies have found that these gains in disability-free life expectancy have been accompanied by an increase in the prevalence of chronic diseases [42,43].…”
Section: Healthier? -Demographic Change and Healthy Life Expectancymentioning
confidence: 99%